2023
DOI: 10.1002/jsfa.12526
|View full text |Cite
|
Sign up to set email alerts
|

Different diagnostic approaches for the characterization of the fungal community and Fusarium species complex composition of Italian durum wheat grain and correlation with secondary metabolite accumulation

Abstract: BACKGROUND The evolution of the fungal communities associated with durum wheat was assessed using different diagnostic approaches. Durum wheat grain samples were collected in three different Italian cultivation macro‐areas (north, center and south). Fungal isolation was realized by potato dextrose agar (PDA) and by deep‐freezing blotter (DFB). Identification of Fusarium isolates obtained from PDA was achieved by partial tef1α sequencing (PDA + tef1α), while those obtained from DFB were identified from their mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…As ruling species may change in time, for example, in North Europe the F. culmorum, F. avenaceum or F. langsethiae Torp and Nirenberg will be replaced by F. graminearum , resistance relations become important [ 36 , 60 , 61 ]. Senatore et al [ 62 ] tested 70 Italian wheat samples for multitoxin analyses: 24 different species were identified, and the most frequent were F. graminearum and F. avenaceum with about equal weight followed F. poae , F. proliferatum by PDA + tef1a, and 24 Fusarium spp. were detected by the DFB + mc method.…”
Section: The Causing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ruling species may change in time, for example, in North Europe the F. culmorum, F. avenaceum or F. langsethiae Torp and Nirenberg will be replaced by F. graminearum , resistance relations become important [ 36 , 60 , 61 ]. Senatore et al [ 62 ] tested 70 Italian wheat samples for multitoxin analyses: 24 different species were identified, and the most frequent were F. graminearum and F. avenaceum with about equal weight followed F. poae , F. proliferatum by PDA + tef1a, and 24 Fusarium spp. were detected by the DFB + mc method.…”
Section: The Causing Agentsmentioning
confidence: 99%
“…It seems that we do not simply encounter a single mycotoxin occurrence in our wheat and wheat products; usually, there are more [ 62 ]. Varga et al [ 63 ] reported from Hungary between 1994 and 2002 9689 toxin analyses from cereals, including wheat.…”
Section: Multi Mycotoxin Contamination In Freshly Harvested and Store...mentioning
confidence: 99%
“…The maximum and minimum values were given in some papers but are often absent. We speak about food and feed safety, but most papers discussed only visual symptoms; for example, the fungal mass determined based on quantitative PCR data or other means were reported in several cases, and exceptionally, like in wheat, toxin data showed rather close correlations between fungal mass and toxin content [13]. Toxin data are included rather exceptionally.…”
Section: Introductionmentioning
confidence: 99%